The composition of a function g with a function f is :
h(x) = g(f (x))
The domain of h is the set of all x-values such that x is in the domain of f and f (x) is in the domain of g.
Let f(x) = 2x – 1, g(x) = 3x, and h(x) = x2 + 1.Compute the following :
Problem 1 :
f(g(-3))
Solution :
f(x) = 2x – 1 and g(x) = 3x
Apply x = -3 in g(x) g(-3) = 3(-3) g(-3) = -9 f(g(-3)) = f(-9) |
Apply x = -9 in f(x) f(-9) = 2(-9) – 1 = -18 – 1 f(-9) = -19 |
f(g(-3)) = -19
Problem 2 :
f(h(7))
Solution :
f(x) = 2x – 1
h(x) = x2 + 1
f(h(7)) = ? Apply x = 7 in h(x) h(7) = (7)2 + 1 h(7) = 49 + 1 h(7) = 50 |
f(h(7)) = f(50) Apply x = 50 in h(x). = 2(50) – 1 = 100 – 1 f(h(7)) = 99 |
f(h(7)) = 99
Problem 3 :
(g ∘ h)(24)
Solution :
g(x) = 3x
h(x) = x2 + 1
(g ∘ h)(24) = g(h(24))
Apply x = 24 in h(x) h(24) = (24)2 + 1 = 577 |
g(h(24)) = g(577) Apply x = 577 in g(x) = 3(577) = 1731 |
(g ∘ h)(24) = 1731
Problem 4 :
f(g(h(2)))
Solution :
f(x) = 2x – 1
g(x) = 3x
h(x) = x2 + 1 and f(g(h(2))) = ?
Apply x = 2 in h(x) h(2) = (2)2 + 1 h(2) = 5 |
g(h(2)) = g(5) Now apply x = 5 in g(5) = 3(5) g(5) = 15 |
f(g(h(2))) = f(15)
Apply x = 15 in f(x).
= 2(15) – 1
f(g(h(2))) = 29
Problem 5 :
h(g(f(5)))
Solution :
Given functions are f(x) = 2x – 1, g(x) = 3x and h(x) = x2 + 1
h(g(f(5))) = ?
Apply x = 5 in f(x) f(5) = 2(5) – 1 f(5) = 9 |
g(f(5)) = g(9) Apply g(9) in g(x) = 3(9) g(9) = 27 |
h(g(f(5))) = h(27)
= (27)2 + 1
= 730
h(g(f(5))) = 730
Problem 6 :
g(f(h(-6)))
Solution :
Given functions are (x) = 2x – 1, g(x) = 3x and h(x) = x2 + 1
g(f(h(-6))) = ?
Apply x = -6 in h(x) h(-6) = (-6)2 + 1 h(-6) = 37 f(h(-6)) = f(37) |
Apply x = 37 in f(x). = 2(37) – 1 = 74 – 1 = 73 |
g(f(h(-6))) = g(73)
= 3(73)
= 219
g(f(h(-6))) = 219
Problem 7 :
If f(x) = 3x - 5 and g(x) = x2, find (f ∘ g)(3)
Solution :
f(x) = 3x - 5 and g(x) = x2
(f ∘ g)(x) = f(g(x))
(f ∘ g)(3) = f(x2)
= f(32)
f(9) = 3(9) – 5
= 27 – 5
= 22
Problem 8 :
If f(x) = -9x - 9 and g(x) = √(x – 9), find (f ∘ g)(10)
Solution :
f(x) = -9x - 9, g(x) = √(x – 9)
(f ∘ g)(10) = ?
(f ∘ g)(x) = f(g(x)) (f ∘ g)(10) = f(g(10)) g(10) = √(10–9) = 1 |
(f ∘ g)(10) = f(1) = -9(1) – 9 = -9 – 9 = -18 (f ∘ g)(10) = -18 |
Problem 9 :
If f(x) = -4x + 2 and g(x) = √(x – 8), find (f ∘ g)(12)
Solution :
f(x) = -4x + 2, g(x) = √(x – 8)
(f ∘ g)(12) =?
(f ∘ g)(x) = f(g(x)) (f ∘ g)(12) = f(g(12)) g(12) = √(12 – 8) g(12) = √4 g(12) = 2 |
(f ∘ g)(12) = f(2) = -4(2) + 2 = -8 + 2 = -6 (f ∘ g)(12) = -6 |
Problem 10 :
If f(x) = -3x + 4 and g(x) = x2, find (g ∘ f)(-2)
Solution :
f(x) = -3x + 4
g(x) = x2
(g ∘ f)(x) = g(f(x)) (g ∘ f)(-2)= g(f(-2)) f(-2) = -3(-2) + 4 = 6 + 4 = 10 |
(g ∘ f)(-2)= g(10) = (10)2 = 100 (g ∘ f)(-2) = 100 |
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM